Research and Practice of Building a Personalized Recommendation System for Mobile Game Platform Based on Big Data Mining - Hailang You; Feng Qian; Xiangwei Huang; Liangliang Hu (Dianxin kexue)
The personalized recommendation system was presented, which was based on data mining technology in mobile game platform, including the game data acquisition, data storage, data cleaning, data mining, and the cosine similarity algorithm was used to improve the similarity of the games. The mechanism can effectively improve the accuracy of game recommendation, enhance user stickiness, and create more value for the game platform.